Asthma, airways responsiveness and air pollution in two contrasting districts of northern England. Issue 2 (February 1996) - Devereux, G.; Ayatollahi, T.; Ward, R.; Bromly, C.; Bourke, S. J.; Stenton, S. C.; Hendrick, D. J.
Abstract : BACKGROUND: To assess the possible magnitude of differences between normal populations an epidemiological investigation of asthma was conducted in two strongly contrasting districts of northern England–rural West Cumbria on the west coast and urban Newcastle upon Tyne on the east coast. METHODS: A cross sectional survey of randomly identified men aged 20-44 years was conducted in two phases: phase 1, a postal survey of respiratory symptoms and asthma medication in 3000 men from each district; and phase 2, a clinical assessment of 300 men from each district comprising investigator administered questionnaires, skin prick tests, spirometry, and methacholine challenge tests. RESULTS: The phase 1 (but not phase 2) study showed a small excess of "ever wheezed" in Newcastle (44% versus 40%), but neither phase showed differences between the two districts for recent wheeze or for other symptoms characteristic of asthma. There were also no differences with regard to diagnosed asthma, current asthma medication, spirometric parameters, or airways responsiveness. The prevalence of quantifiable airways responsiveness (PD20 < or = 6400 micrograms) was 27.7% in West Cumbria and 28.2% in Newcastle. Regression analyses showed that PD20 was negatively associated with atopy and positively with forced expiratory volume in one second (FEV1); that an association between PD20 and current smoking could be explained by diminished FEV1; and that PD20 was not related to geographical site of residence. CONCLUSIONS: Neither airways responsiveness nor the other parameters of diagnostic relevance to asthma varied much between the two study populations, despite the apparent environmental differences. The most obvious of these were the levels of outdoor air pollution attributable to vehicle exhaust emissions, the ambient levels of which were 2-10 fold greater in Newcastle. Our findings consequently shed some doubt over the role of such pollution in perceived recent increases in asthma prevalence. It is possible, however, that an air pollution effect in Newcastle has been balanced by asthmagenic effects of other agents in West Cumbria.